The Position of Witnesses in Syariah and Civil Courts: Proceedings in Malaysia - Al 'Uyuna Bt Mohd Amin (Universiti Sains Islam Malaysia, 2022)
This library research provides an in-depth discussion of the position of witnesses in Syariah and Civil courts, proceedings in Malaysia. The study sought to find the problems and gaps pertaining to the position of witnesses in the Syariah and civil courts in the Malaysian Legal System. The writer also researched the position of witnesses based on The Law of Allah (Hukum Syarak) and the current Law of Evidence. Observations, specialist informants, documents, lists of cases and enactments which are related to the study were tools employed for data gathering purposes. The findings indicate that there are many contradictions and gaps among witnesses in both courts such as the conditions for being witnesses, the number of witnesses and the examination of witnesses. The study found that there are many changes and improvements that need to be taken which are preventing the effectiveness of Malaysian system of justice. At the end of this research, the writer has given recommendations, ideas and some suggestions and solutions in order to make sure that the Malaysian Legal System is excellent based on the Law of Allah (Hukum Syarak).